Fatal toxoplasmic encephalitis triggered by anti-TNF therapy - Rodrigo A. Montoro; Michael Moran; Katherine A. Overmyer; Andrew Periaccante; Joshua J. Coon; Swapnil Lanjewar; Laura J. Knoll; Rob Striker (Heliyon)
Reactivation of a latent infection by the protozoan parasite Toxoplasma gondii can result in severe neurologic outcomes and even death. T. gondii reactivation cases have been strongly associated with acquired immunodeficiency syndrome, but other immunosuppressive situations are also associated. Anti-TNF-α therapy reliably triggers the reactivation of T. gondii latent cysts in mice models. Reactivation of T. gondii by TNF-a blockade is rare in humans though despite widespread use of TNF-a blockers. Serologic evidence of a possible latent T. gondii infection in humans is common worldwide, so why anti-TNF-α reactivation isn't more common is unknown. Here we present a 74-year-old woman who developed fatal cerebral toxoplasmosis after anti-tumor necrosis factor-α (TNF-α). After presenting to a local urgent care with confusion, a worsening cognitive status led to an emergency room visit. Computed tomography resulted in suspicion of metastatic disease leading to treatment with steroids. Lumbar puncture ruled out bacterial or viral meningitis. With continued cognitive decline, magnetic resonance imaging of the head revealed an increased number of lesions with T. gondii-associated ring-enhancing lesions. A brain biopsy confirmed the presence of T. gondii parasites. Despite standard treatment for toxoplasmosis, the patient expired. At least two possible factors may have contributed to this unfortunate outcome. First, in addition to her rheumatoid arthritis pathology, there is evidence of loss of immune resilience and abnormal T cell subsets. Second, some strains of T. gondii are more virulent than others. Post-mortem mass spectrometry and proteomic analysis of her cerebrospinal fluid show several T. gondii peptides. A literature review suggests that risks associated with anti-TNF-α therapy for patients who are seropositive for T. gondii have not been adequately recognized. We advise T. gondii seropositivity testing be considered before and after initiation of anti-TNF-α therapy as is done for other infections such as tuberculosis.